Are beta‐blockers safe to use in patients with asthma or COPD?. Issue 6 (June 2015) - Virani, Zahra; McGarry, Barbara Jo; Roemheld‐Hamm, Beatrix
Abstract : Evidence‐based answer : Beta‐blockers (cardioselective and nonselective) appear safe in patients with mild to moderate asthma or chronic obstructive pulmonary disease (COPD) and do not produce significant adverse respiratory effects (SOR: A, systematic review of RCTs). Betablockers are not associated with increased hospital admissions or length of stay and are, in fact, associated with fewer outpatient clinic visits. Avoiding beta‐blockers in patients with asthma or COPD who present with acute coronary syndrome is associated with increased mortality (SOR: B, cohort studies).